Motor Conduction Studies and Handgrip in Hereditary TTR Amyloidosis: Simple Tools to Evaluate the Upper Limbs - Di Stefano, Vincenzo; Thomas, Ewan; Giustino, Valerio; Iacono, Salvatore; Torrente, Angelo; Pillitteri, Guglielmo; Gagliardo, Andrea; Lupica, Antonino; Palma, Antonio; Battaglia, Giuseppe; Brighina, Filippo (Frontiers in Neurology, 2022)
Purpose Hereditary transthyretin amyloidosis with polyneuropathy (ATTRv) is caused by mutations in the TTR gene, leading to misfolded monomers that aggregate generating amyloid fibrils. The clinical phenotype is heterogeneous, and characterized by a multisystemic disease affecting the sensorimotor and autonomic functions along with other organs. Materials and Methods All the patients were assessed by complete neurological assessment, neurophysiological evaluation, of the median nerve, and handgrip analysis. The data are presented as means and standard deviations. Parametric and non-parametric assessments have been performed to identify differences between groups. Pearson's correlation has been carried out when appropriate. Results Twenty patients with ATTRv (66.1 ± 8.4 years; eight females) and 30 controls (61.1 ± 11.6 years; 16 females) were enrolled. Handgrip strength was reduced in patients with ATTR in both right and left hands compared to the controls. Significant differences were found between patients and controls in the right (handgrip right, HGSR TTR 21.1 ± 13 kg vs. HGSR Control 29.4 ± 11.3 kg, p = 0.017) and left (handgrip left, HGSL TTR 22.2 ± 10.7 kg. vs. HGSL Control 31 ± 11.3 kg, p = 0.007). NIS and CMAP amplitude of the median nerve were related to HGS measures for both hands in patients with ATTRv. Conclusions The progression of bilateral carpal tunnel syndrome is related to neurophysiological data in the median nerve in ATTRv. Also, handgrip measures might represent an important tool for the assessment of disease progression in ATTRv. We propose using a combination of CMAP amplitude and HGS for the assessment of hand motor strength in ATTRv.